The boxcar children beginning eaudiobook The aldens of fair meadow farm. - MacLachlan, Patricia (The Boxcar Children, 2012)
Before they were the Boxcar Children, Henry, Jessie, Violet, and Benny Alden lived with their parents on Fair Meadow Farm.